ESTUDIO DIAGNÓSTICO DEL SERVICIO DE ATENCIÓN A CLIENTES DE UNA AGENCIA AUTOMOTRIZ TABASQUEÑA - Ascencio, Erick Alejandro Gutiérrez; Álvarez, María Cruz Cuevas (IJRDO - Journal of Social Science and Humanities Research, 2022)
OBJECTIVE: The objective is to develop a diagnostic study of customer service in the SUAUTO self-financing area in the Chevrolet Tabasco organization, to determine the areas of opportunity and improvement of the quality of its services. MATERIALS AND METHOD: The present research work is a report from a dissertation. The field work for the dissertation was carried out in the period from May to July 2021 under quantitative and qualitative approaches, descriptive cross-sectional and diagnostic design. The techniques used were a survey, a documentary review, and table of contents. The survey was administered to 103 participants under convenience sampling, and formed by 13 items and a Likert scale from 1-5. The method of information analysis was made with a SWOT matrix, and an Ishikawa diagram; from which the strategies suggested are proposed, as well as a task monitoring process and the responsible areas for that purpose. RESULTS: There is customer satisfaction in terms of payments and promotions, however, they are not pleased with the conditions. This reward and punishment relationship is something that is not well accepted among customers. CONCLUSIONS: An improvement in internal communication between collaborators is required so that the sales force informs its clients about the pre-sale and post-sale processes, complying with certain values ​​defined by the company in question. The credit area is expected to be more effective in its response processes, payments, and units to be delivered, thereby reducing the misinformation that may arise.